Pengaruh Model Problem Based Learning Bermuatan Potensi Lokal Geplak terhadap Keterampilan Berpikir Kritis - Safira Adella Fasya; Maryati (PT. Komunitas Peneliti Alinea, 2026)
The low critical thinking skills of students in Indonesia are caused by students who are not yet able to use their reasoning skills to analyze, evaluate, and provide answers that do not include reasons that support problem solving. This study aims to (1) determine the differences in critical thinking skills of students using the Problem-Based Learning model, which focuses on the local potential of Geplak, a traditional food, compared to the Discovery Learning model. (2) determine the effect of the Problem-Based Learning (PBL) model, which focuses on the local potential of Geplak, on additives, on critical thinking skills. This type of research is a quasi-experimental design with a Non-equivalent pretest-posttest group design, implemented at SMP Negeri 2 Wates. Sampling used a cluster random sampling technique. The sample consisted of 64 eighth-grade students divided into experimental and control groups. Data collection techniques were carried out using test instruments (pretest and posttest critical thinking skills) and non-test (learning implementation observation sheets). Data analysis techniques included learning implementation analysis, descriptive statistical analysis, prerequisite tests (normality and homogeneity tests), n-gain tests, and hypothesis tests (independent sample t-test and effect size). The results of the study indicate that: (1) there is a difference in the critical thinking skills of students who use the Problem Based Learning model containing the local potential of geplak compared to students who use the Discovery Learning model, with a significance value of 0.001 (Sig. < 0.05); (2) there is an effect of implementing the Problem Based Learning model containing the local potential of geplak on critical thinking skills, with a Cohen's α value of 1.0, which is in the moderate category. These findings indicate that PBL containing local potential of geplak effectively improves students' critical thinking skills.